THE RELATION BETWEEN GUT MICROBIOTA AND OBESITY AMONG CHILDREN IN WEST LOMBOK, WEST NUSA TENGGARA, INDONESIA - Siti Helmyati; Setyo Utami Wisnusanti; Maria Wigati; Endri Yuliati (Balai Penelitian dan Pengembangan Kesehatan Magelang, 2019)
Background. Obesity in children makes the higher risk of micronutrients deficiency, increase profile lipid, and promote cell inflammation. Some studies report that gut microbiota may have roles in body metabolism include obesity. Our study aimed to compare the number of Lactobacillus, Bifidobacteria, Escherichia coli, and Enterobacter between obese, normal, and wasted children. Methods. The study was performed in 115 healthy children in West Lombok, West Nusa Tenggara, Indonesia. The total number of bacteria was counted using a culture technique with selective media and total plate count method. Dietary intake assessed to all subjects using a semi-quantitative food frequency questionnaire. Data were analyzed using one-way ANOVA between three groups. Results. The result showed a significant difference in the number of Escherichia coli between obese, normal, and wasted children (p= 0.02), meanwhile there were no significant differences of dietary intake and the number of Lactobacillus, Enterobacter, and Bifidobacteria between the three groups. A potential mechanism by which dysbiosis may cause obesity is its ability to produce short-chain fatty acid (SCFA) by fermentation in the colon. It may increase gut permeability, ghrelin secretion, or bind to toll-like-receptor which leads to enhancement of free fatty acid, cholesterol, and adipose tissue synthesis. Conclusion. Dysbiosis often happened in obese children. Obese children tend to have an imbalance of gut microbiota. However, it needs further study to assess the effects of certain gut microbiota on dietary intake and their effects on obesity cases among children. Keywords: children, dysbiosis, gut microbiota, obesity